Education of biomedical engineering in department of radio and electronics in FEI SUT Bratislava - Lovás, Stanislav; Ondráček, Oldřich; Cocherová, Elena; Púčik, Jozef; Šurda, Jozef (Lékař a technika, 2008)
The paper is focused on presentation of the biomedical engineering education in Department of Radio and Electronics in FEI SUT Bratislava. Annotations of particular specialized subjects oriented at biomedicine and biosignal processing are introduced. Students have opportunity to choose from diff erent subjects, which provide analytic and diagnostic methods of signal processing, such as team projects and diploma thesis, or microcontrollers and signal processors.
Keywords: bionika; Signal Processing, Computer-Assisted; Telemedicine; biomedicínské inženýrství; počítačové zpracování signálu; biofyzika; Education, Professional; Slovakia; diagnostické techniky a postupy; lidé; Electronics, Medical; Diagnostic Techniques and Procedures; Biophysics; telemedicína; vzdělávání odborné; Electromagnetic Phenomena; studium vysokoškolské; elektromagnetické jevy; Bionics; Education, Graduate; Biomedical Engineering; Slovenská republika; lékařská elektronika; Humans